Stress and Burnout Among Frontline Nurses During COVID-19 Pandemic in a Middle Eastern Country - Ester Mary Pappiya RN, RM, MSC (N); Ibrahim Mubarak Al Baalharith MSN; Judie Arulappan RN, RM, MSC (N); Sahbanathul Missiriya Jalal RN, RM, MSC (N); Krishnaraju Venkatesan PhD; Hamad Salem Al Grad MSN; Abdullaah Baraik S. Alawad MSN (SAGE Publishing, 2023)
Introduction The COVID-19 pandemic has resulted in an unanticipated shift in nursing practice to meet the sudden increase in demand for pandemic-related care, leaving nurses unable to provide acceptable services to patients in the way they were taught and expected to do. It put the nurses under more stress and most of them were dissatisfied with their work due to excessive burnout. Objectives The study determined the level of stress and burnout among front-line nurses working at the Ministry of Health Hospitals in Najran, Saudi Arabia during the COVID-19 pandemic. Methods A total of 1594 nurses were chosen using a convenience sampling approach. Google Forms were used to collect data from the nurses. COVID-19 stressors questionnaire and an abbreviated Maslach Burnout Inventory were used to assess stress and burnout among nurses. Results Our study reported that the majority of nurses experienced extreme levels of stress as their colleagues became ill; that they would spread COVID-19 infection to their family and friends; upsetting to see COVID-19 patients dying in front of them; not knowing when the COVID-19 pandemic will be under control; and emotional exhaustion and physical fatigue. A vast majority of nurses felt there were not adequate protective measures; there was a shortage of staff at times; were nervous and scared and thought of quitting their job; and they would quit their job if a COVID-19 outbreak recur and they would fall sick. Likewise, 41.9% of the nurses experienced a high level of burnout. A significant association was found between the area of working and the level of burnout among nurses. Conclusion As nurses experienced extreme levels of stress and severe burnout, it is vital to design regular programs to assist frontline nurses in maintaining their mental health.